Pathogenetic role of vitamin D deficiency and immune-inflammatory disorders in development of fetal distress in pregnant women with chronic hydramnion - Haistruk, N. A.; Haistruk, A. N.; Melnyk, A. V.; Dubas, L. H.; Lovkina, O. L. (Zaporozhye Medical Journal, 2019)
The role of vitamin D deficiency and immune-inflammatory disorders in the mechanisms of fetal distress development in pregnant women with chronic polyhydramnios remains unstudied. Objective: to evaluate the role of vitamin D deficiency and associated immune inflammatory disorders in the development of fetal distress in pregnant women with chronic polyhydramnios. Materials and methods. In total, 30 women with a physiological course of pregnancy and 90 pregnant women with chronic polyhydramnios were examined. The serum levels of vitamin D metabolite (25 (OH)D) and cytokines IL-10 and IL-6 were determined by enzyme immunoassay using standard kits. Statistical processing of the obtained results was performed using standard methods with MS Excel and Statistica SPSS 10.0 for Windows application package. Results. In pregnant women with chronic polyhydramnios, there is a significant decrease in the serum level of vitamin D metabolite 25 (OH)D by 21 % and anti-inflammatory cytokine IL-10 by 26.4 %, and an increase in the concentration of pro-inflammatory IL-6 by 17 % compared to women with physiological course of pregnancy. The occurrence of fetal distress in chronic polyhydramnios is accompanied by worsening of vitamin D deficiency and immune-inflammatory disorders: the levels of 25 (OH)D and IL-10 are 18.5 % and 17.5 % decreased, respectively, and IL-6 is 13.3 % increased than in women with chronic polyhydramnios without fetal distress. The intensity of immune disorders in pregnant women with chronic polyhydramnios is determined by the level of vitamin D in the organism. Thus, in women with 25 (OH)D deficiency, a significant decrease in serum IL-10 concentration by 47.8 % and a significant increase in IL-6 by 34.6 % were recorded in comparison with these indicators in women with vitamin D deficiency. Conclusions. Vitamin D deficiency and associated immune-inflammatory disorders play an important role in the development of fetal distress in pregnant women with chronic polyhydramnios.